Imprisonment and Fine Sentence Inequivalence in Netherland’s Criminal Law - Teng Junaidi Gunawan,; Made Warka,; Otto Yudianto,; Erny Herlin Setyorini, (Technium Social Sciences Journal, 2021)
In the effort of renewing Indonesian criminal law; or criminal justice, which until now there is an empty norm that can rationally explain the crime perpetrator is convicted to a sentence of 2 years imprisonment, 3 months of imprisonment, or criminal fine of a certain amount, this study proposed a finding of above-mentioned research’s idea with micro comparisons between Indonesian and Netherland criminal law and criminal sentencing. This normative legal research is part of a larger study, namely the equivalent formulations formulation of imprisonment and fines, which in this study discuss the findings of imprisonment and criminal fine inequality, including violations to the theory of double track or dualistic sentencing system in Netherland. The analysis of criminal sanctions in the Netherlands uses economic analysis of criminal / penal sentence. With legal research approach of statute approach and micro comparison approach between Indonesian and Dutch criminal law, the same weaknesses that greatly influence criminal law to apply restorative justice both in Indonesia and; especially in this writing, in the Netherlands. Without prison and fine criminal equivalency, and criminal fine that is too low as alternative penal sanctions to imprisonment; that are worthy of being convicted to the perpetrator, the judge will be reluctantly impose the fine sentence, in such that it pushes the end result of criminal justice only to the option of hurting the perpetrator rather than to restore conditions caused by the damages of a crime.